2023
DOI: 10.1007/s00421-022-05125-9
|View full text |Cite
|
Sign up to set email alerts
|

Defining left ventricular remodeling using lean body mass allometry: a UK Biobank study

Abstract: Purpose:The geometric patterns of ventricular remodeling are determined using indexed left ventricular mass (LVM), end-diastolic volume (LVEDV) and concentricity, most often measured using the mass to volume ratio (MVR). The aims of this study were to validate lean body mass (LBM) based allometric coefficients for scaling and to determine an index of concentricity that is independent of both volume and LBM.Methods: Participants from the UK Biobank who underwent both CMR and dual-energy x-ray absorptiometry (DX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…It is recognized that VO 2 is more directly associated with FFM than total body weight, as fat mass has a minimal contribution to peak oxygen consumption 15,22 . As Jackson et al demonstrated and we replicated in our simulation, the BMI versus fat mass percentage relationship is mostly linear for populations with a BMI < 30 kg/m 2 and becomes non‐linear at higher BMIs 16 .…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…It is recognized that VO 2 is more directly associated with FFM than total body weight, as fat mass has a minimal contribution to peak oxygen consumption 15,22 . As Jackson et al demonstrated and we replicated in our simulation, the BMI versus fat mass percentage relationship is mostly linear for populations with a BMI < 30 kg/m 2 and becomes non‐linear at higher BMIs 16 .…”
Section: Discussionsupporting
confidence: 69%
“…Comparing pVO 2 indexed to FFM allows for a better evaluation of the fitness assumptions of the different predictive equations as pVO 2 is more influenced by FFM and less by an individual's percentage fat composition 21 . To derive FFM, data from 1057 and 581 apparently healthy female and male subjects participating in the UK Biobank project, respectively, who underwent dual‐energy x‐ray absorptiometry (DEXA) imagining between August 2014 and 2015 were used (project: 22282 genetic and environmental determinants of exercise capacity and fitness) 22 . Importantly, this FFM estimate considered the non‐linear relationship between total body weight and percent body fat which allowed for a more accurate model of FFM in those with high BMI.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation